The Protective Effects of the Combination of Vitamin E and Swimming Exercise on Memory Impairment Induced by Exposure to Waterpipe Smoke - Alzoubi, Karem H.; Halboup, Abdulsalam M.; Khabour, Omar F.; Alomari, Mahmoud A. (Bentham Science, 2022)
Background: Waterpipe smoking (WP) exposure involves a negative health impact, including memory deficit, which is attributed to the elevation of oxidative stress. Vitamin E (VitE) in combination with swimming exercise exerts protective effects that prevent memory impairment. In the current study, the modulation of WP-induced memory impairment by the combined effect of VitE and swimming exercise (SE) was investigated. Methods: Animals were exposed to WP one hour/day, five days per week for four weeks. Simultaneously, VitE (100 mg/kg, six days/week for four weeks) was administered via oral gavage, and the rats were made to swim one hour/day, five days/week for four weeks. Changes in memory were evaluated using radial arm water maze (RAWM), and oxidative stress biomarkers were examined in the hippocampus. Results: WP exposure induced short-term/long-term memory impairment (p<0.05). This impairment was prevented by a combination of VitE with SE (p<0.05). Additionally, this combination normalized the hippocampal catalase, GPx, and GSH/GSSG ratios that were modulated by WP (p<0.05). The combination further reduced TBARs levels below those of the control group (p<0.05). Conclusion: WP-induced memory impairments were prevented by the combination of VitE with SE. This could be attributed to preserving the hippocampal oxidative mechanism by combining VitE and SE during WP exposure.